A BRIEF OVERVIEW ABOUT THE DEVELOPMENT OF TORSIONAL VIBRATION CALCULATION AND EDUCATION OF METHODS FOR THEIR CALCULATION - Václav ZOUL; Petar KOVÁČ (Scientific Journal of Silesian University of Technology. Series Transport)
Torsional vibration calculation (TVC) is among the basic calculations that are required to support propulsion projects for various vehicles, ships and construction machines. A number of powerful software packages for these calculations already exists. However, the need to respect the physical properties of propulsion systems that are more complex than before has arisen. At the same time, knowledge about system properties and the capabilities of computing systems are also growing, resulting in an increase in new software systems, which could be used for these calculations. In this paper, these new trends are briefly described, with attention paid not only to practical use, but above all to how and to what extent these themes should be presented to students.